Case Report: IgG4-related ophthalmic disease presenting with unilateral proptosis - Li, Xiaodong; Qin, Xuewei; Chen, Mei; Zheng, Xi (Frontiers in Immunology, 2025)
IgG4-related eye disease (IgG4-ROD) is characterized by diffuse swelling or well-defined masses in the lacrimal glands, extraocular muscles, and eyelids, often accompanied by eyelid swelling, proptosis, and diplopia. It typically affects both sides symmetrically and can mimic various infectious, inflammatory, and neoplastic diseases. Early recognition and steroid therapy can significantly improve symptoms, but recurrence is common, necessitating careful and long-term follow-up. B-cell depletion therapy, such as rituximab, is increasingly being incorporated into standard treatment protocols. This article reports a case of IgG4-ROD misdiagnosed as a unilateral orbital mass, summarizing its clinical features, diagnostic approach, and treatment outcomes. Combined with a literature review and analysis, this study aims to provide reference for the clinical identification of IgG4-ROD.